Kidney Function Improvement by Soy Milk Containing Lactobacillus plantarum A7 in Type 2 Diabetic Patients With Nephropathy: a Double-Blinded Randomized Controlled Trial (Iranian Journal of Kidney Diseases, 2017)
Introduction. Even with the ultimate medical management, more than one-third of diabetic patients develop diabetic nephropathy. To our knowledge, there is no study that has examined the effect of probiotic soy milk on kidney function in type 2 diabetic patients with nephropathy. This clinical trial aimed to assess the effects of consumption of probiotic soy milk, compared with conventional soy milk, on kidney-related indexes in patients with diabetic nephropathy. Materials and Methods. In a randomized double-blinded placebo-controlled trial, 44 patients were randomly assigned to receive 200 mL/d of either soy milk containing Lactobacillus plantarum A7 or conventional soy milk for 8 weeks. Primary endpoints included urinary albumin excretion, estimated glomerular filtration rate, interlukin-18, serum sialic acid, and serum creatinine. Fasting blood samples and morning fasting spot urine samples were collected at the beginning and after 8 weeks for evaluation of biochemical parameters. Results. Forty patients completed the study. Administration of probiotic soymilk resulted in a significant reduction in albuminuria (P = .03), serum creatinine (P < .001), serum interleukin-18 (P = .002), and serum sialic acid (P = .001) compared with conventional soy milk. Probiotic soymilk supplementation also led to a significant improvement in estimated glomerular filtration rate (15.9 ± 10.8 mL/min versus 3.2 ± 8.4 mL/min, P < .001) compared with the control group. Conclusions. Probiotic soy milk was safe and well-tolerated by patients with diabetic nephropathy for 8 weeks. Probiotic soy milk also improved indexes of kidney function in type 2 diabetic patients with nephropathy.